The Teacher Communication Patterns with Students in Moral Development at SDN Puhrubuh 1 Kediri Regency District - Zuliati, Adib; Jannah, Siti Roudhatul (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This research was motivated by curiosity about the communication patterns of Islamic Religious Education Teachers at SDN Puhrubuh 1, Semen District, Kediri Regency towards their students so that they are able to shape the character of their students into people with noble character. This research aims to; found communication patterns between teachers and students that were built in the school so that religious character and morals were formed as a whole in this school. The method used in this research is a descriptive qualitative research method, the data collection techniques used are observation, reading online literature. Analyzing data by reducing data, presenting data, and drawing conclusions. The research results show an oral communication pattern by maintaining gentle speech, not using harsh words, an exemplary communication pattern by frequently telling exemplary stories of the Prophet while practicing it in everyday life. Indicators that can be seen in the field are the friendliness of all school residents, the principal, teachers, security and students, greetings, friendly smiles, and the school environment.